Kelulushidupan Biota pada Sistem Integrated Multi Trophic Aquaculture (IMTA)-Padi - Hamsiah Hamsiah; Indra Cahyono; Heriansah Heriansah; Wayan Kantun; Arnold Kabangnga (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Survival rate is a determinant factor of success in multibiota cultivation. This study aims to determine the survival rate of biota cultivated in various combinations in the Integrated Multi Trophic Aquaculture (IMTA)-Paddy system. Three combinations (K) of biota and three replications, namely milkfish and paddy(K-2), milkfish, tiger prawns, and paddy (K-3), and milkfish, tiger prawns, and shellfish (K-4) were investigated experimentally in the field using a tarpaulin pond model. Biota was reared for 80 days with a density of 30 individuals each integrated with 30 clumps of rice by floating method. The results showed that the difference in the survival rate of milkfish at K-2 (97.8±1.91%), K-3 (94.4±1.96%), and K-4 (98.9±1.90%) was in the range of 1.1- 3.6% which was not statistically significant (P> 0.05). The survival rate of tiger prawns in K-4 (88.9±1.91%) was descriptively 2.2% higher than K-3 (86.7±1.90%). The survival rate of shellsfish on K-4 biota is 85.6±1.90%. Water quality during experimental is in the range that can be tolerated by each biota. More research is needed which in-depth to optimize the IMTA-Paddy system in brackishwater.